Strengthening Subnational Debt Financing and Managing Risks - Liu, Lili (World Bank, Washington, DC, 2014)
The Chinese budget law prevents subnational governments from borrowing. However, Subnational Governments (SNG) borrows indirectly off-budget, through Urban Development and Investment Corporations (UDIC). There are various estimates on the off-budget liabilities, with one estimate having the liabilities at more than 30 percent of Gross Domestic Product (GDP). This paper provides a discussion of more reform options for China, anchored with cross-country experiences and lessons. The way forward is to develop regulatory frameworks that can expand SNG and UDIC market access and debt financing, while strengthening subnational fiscal discipline, managing default risks, promoting capital market development, and supporting macroeconomic management and a stable financial system. The paper is organized as: section two presents fiscal rules and framework - ex ante regulations for subnational debt issuing and procedures. Section three discusses what to do when a subnational government becomes insolvent - ex post system. Section four is devoted to developing regulatory frameworks for UDIC, which may require a debt restructuring system different from a system for direct debt of SNG. Ex post debt restructuring for UDIC may also differ from the existing bankruptcy code in China for corporations due to the fundamental difference between a public entity and a private corporation. Section five focuses on strengthening debt management capacity of SNG particularly with respect to liquidity and refinancing risks. Section six focuses on managing fiscal risks of land financing, given its prevalent use in China. Section seven discusses the development of a competitive and diversified subnational debt market. Section eight concludes with suggested reform options.